2017
DOI: 10.1182/blood-2016-12-754051
|View full text |Cite
|
Sign up to set email alerts
|

SCL/TAL1: a multifaceted regulator from blood development to disease

Abstract: SCL/TAL1 (stem cell leukemia/T-cell acute lymphoblastic leukemia [T-ALL] 1) is an essential transcription factor in normal and malignant hematopoiesis. It is required for specification of the blood program during development, adult hematopoietic stem cell survival and quiescence, and terminal maturation of select blood lineages. Following ectopic expression, SCL contributes to oncogenesis in T-ALL. Remarkably, SCL's activities are all mediated through nucleation of a core quaternary protein complex (SCL:E-prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 129 publications
1
89
0
Order By: Relevance
“…We also show that Nanog directly represses the master hematopoietic regulator Tal1 (Porcher et al, 2017) through an upstream regulatory element located in an intron of the neighboring Stil gene. Interestingly, this site is occupied by NANOG only during the differentiation of ES cells to EpiLCs (Murakami et al, 2016).…”
Section: Discussionmentioning
confidence: 64%
“…We also show that Nanog directly represses the master hematopoietic regulator Tal1 (Porcher et al, 2017) through an upstream regulatory element located in an intron of the neighboring Stil gene. Interestingly, this site is occupied by NANOG only during the differentiation of ES cells to EpiLCs (Murakami et al, 2016).…”
Section: Discussionmentioning
confidence: 64%
“…Since ZFPM2 is a transcriptional cofactor, we extracted from TCGA AML data those genes whose expression is correlated with that of ZFPM2 ( Figure 7C-D) and showed that those genes significantly overlapped with those bound by GATA2 and were enriched in proto-oncogenes and those associated with transcriptional misregulation in cancer ( Figure 7E). As shown in Figure 7F, GATA2 binds to the promoter of one such gene, TAL1, an erythroid differentiation factor (Porcher et al 2017), which suggests that TAL1 expression may be regulated by ZFPM2. Finally, a number of genes frequently altered in our cohort but not previously associated with Figure 7.…”
Section: Resultsmentioning
confidence: 91%
“…In line with this restricted temporal requirement, in vitro studies have demonstrated the critical role of SCL for the formation of haemangioblast [46] and HE [47]. As discussed elsewhere, SCL is also an important player in adult haematopoiesis and erythropoiesis [48].…”
Section: Sclmentioning
confidence: 79%
“…Similar to ETV2, the expression of SCL is only temporally required for blood cell emergence as its conditional deletion in TIE2-expressing cells does not affect blood cell emergence [45]. As discussed elsewhere, SCL is also an important player in adult haematopoiesis and erythropoiesis [48]. As discussed elsewhere, SCL is also an important player in adult haematopoiesis and erythropoiesis [48].…”
Section: Sclmentioning
confidence: 92%